A commercial monovalent canine parvovirus vaccine performs better than a commercial combination vaccine in puppies - Asghar, MU; Anjum, AA; Rabbani, M; Khan, MA; Ali, MA; Azeem, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Thirty puppies were randomly divided in to 3 groups for comparative evaluation of two commercial CPV vaccines. Each group was further subdivided in to < 6 months and < 3 months -old puppies and either vaccinated with a monovalent vaccine: Primodog, a combination vaccine: Duramune or maintained as a non-vaccinated control. Humoral immune response was determined by Hemagglutination Inhibition (HAI) on 21 and 35 -days after vaccination. The geometric mean titer (GMT) induced by Duramune, 21 and 35 -days post-vaccination was GMT 73.3 and 137.2, respectively. Comparatively, Primodog demonstrated higher GMT on 21 and 35 -days after vaccination: 97.0 and 168.9, respectively. The older puppies (< 6 months old) demonstrated higher seroconversion to both vaccines.